Pengaruh Penggunaan Digital Payment terhadap Perilaku Manajemen Keuangan Mahasiswa Pendidikan Ekonomi dengan Literasi Keuangan Digital sebagai Variabel Moderasi - Munawaroh, Iya; Gumilar, Gugum; Kurniawan, Kurniawan (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Financial management behavior is an important skill that every individual should have, especially students who are starting to be independent in managing their finances in order to support their financial independence. The development of financial digitalization has encouraged students to switch to digital payments in daily transactions, maintaining that it is closely related to financial management behavior. Therefore, this study aims to determine the effect of using digital payments on students' financial management behavior with digital financial literacy as a moderating variable. This study uses a quantitative approach with a survey method. The population of this study amounted to 366 economic education students, with a sample size of 188 students. The results showed that: (1) There is a significant effect of using digital payments on student financial management behavior. (2) Digital financial literacy moderates the effect of using digital payments on student financial management behavior (3) Simultaneously, the use of digital payments and digital financial literacy has an influence on student financial management behavior. This study shows that the use of digital payments has a positive and significant effect on student financial management behavior, with digital financial literacy moderating the relationship.